Ellipsometry and optical spectroscopy of low-dimensional family TMDs - Kravets, V.G.; Prorok, V.V.; Poperenko, L.V.; Shaykevich, I.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Here, we report a comprehensive study of the fundamental optical properties of two-dimensional materials. These properties have been ascertained using spectroscopic ellipsometry, optical spectroscopy of Raman scattering, and photoluminescence. We have focused on the optical properties of the chemically exfoliated layered TMDs: MoS₂, MoSe₂, WS₂, and WSe₂. The complex refractive index and optical conductivity within the region 1 to 4.5 eV were extracted, which led to the identification of many unique interband transitions at high symmetry points in the electron band structure. The positions of the so-called A and B excitons in monolayers are found to shift upwards in energy as compared with those of the bulk form and have a smaller separation because of the decreased interactions between the layers. For monolayer TMDs, the valence-band spin-orbit splitting at the K point was estimated from the energy difference between the A and B exciton peaks. Our findings of the spin-orbit coupling of ∼0.16, ∼0.26, ∼0.37, and ∼0.55 eV in monolayers MoS₂, MoSe₂, WS₂, and WSe₂, respectively. All these findings not only extend our understanding of the novel electronic structures of mono- and few-layer TMDs but also provide a foundation for future technological applications of optoelectronic and spintronic device components.